Family matters: the role of parents in adolescent motivation and exercise promotion - Bai, Dan; Wu, Mingdong; Li, Baixia; Zheng, Danheng; Liu, Xiaoming (Frontiers in Pediatrics, 2026)
ObjectivesThis study aimed to investigate the relationship between parents' exercise habits (PEH), exercise motivation (EMO), and exercise behavior (EB) among junior high school students in Shanghai, with a particular focus on the mediating effects of different types of motivation.MethodsA cross-sectional online survey was conducted in Shanghai from February to June 2023 using purposive sampling. A total of 803 questionnaires were distributed through online platforms, and 777 valid responses were included in the final analysis. Structural Equation Modeling (SEM) was applied using SmartPLS 4.0 to examine the direct and indirect pathways among variables.ResultsThe results showed that PEH was positively associated with EB both directly and indirectly. Among the five types of EMO, competence motivation (CMO) and fitness motivation (FMO) were positively related to EB, whereas social motivation (SMO) was negatively related to EB. Mediation analysis indicated that CMO served as a significant positive mediator, while SMO acted as a significant negative mediator in the relationship between PEH and EB. Enjoyment motivation (EJMO) and appearance motivation (AMO) were not significantly associated with EB. In addition, PEH was positively associated with all five dimensions of EMO.ConclusionsPEH play an important role in shaping adolescents' EB through distinct motivational pathways. Autonomous motivations, particularly competence-related motivation, facilitated exercise engagement, whereas socially controlled motivation was associated with lower EB. These findings highlight the need for family- and school-based interventions that emphasize autonomy and competence support rather than social pressure to promote sustained physical activity (PA) among adolescents.